2021
DOI: 10.37992/2021.1202.060
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mutagenic sensitivity in blackgram variety CO 6

Abstract: The present study was conducted to examine the mutagenic effect of 60 Co gamma rays and a combination of 60 Co gamma rays with EMS in blackgram variety CO 6. Based on the LD 50 dose, the seeds were treated with three different doses of gamma rays (200, 300, 400 Gy) and recurrent doses of 20 mM and 30 mM EMS were treated with gamma ray irradiated seeds for combination treatments. The M 1 generation was evaluated in the field for the following parameters viz., germination percentage, plant survival percentage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This is in close agreement with the reports of Dutta et al (2021) in bitter gourd. Tamilzharasi et al (2021) reported that there was a substantial positive correlation between mutation frequency and biological damage in the M1 generation when exposed to gamma radiation in blackgram. Mutagenic effectiveness refers to the rate at which a mutation is induced as a function of the mutagenic dose.…”
Section: Resultsmentioning
confidence: 99%
“…This is in close agreement with the reports of Dutta et al (2021) in bitter gourd. Tamilzharasi et al (2021) reported that there was a substantial positive correlation between mutation frequency and biological damage in the M1 generation when exposed to gamma radiation in blackgram. Mutagenic effectiveness refers to the rate at which a mutation is induced as a function of the mutagenic dose.…”
Section: Resultsmentioning
confidence: 99%